A compact size wide‐angle 3 × 3 substrate integrate waveguide Butler matrix for Ku‐band applications. Issue 6 (19th February 2022) - Fathalizadeh, Mohammad; Sedghi, Tohid; Asadpor, Loghman; Zehforoosh, Yashar
Abstract: In this paper, an array antenna fed by a novel double layer 3 × 3 Butler matrix for Ku‐band application was presented. An antipodal Vivaldi antenna (AVA) with dielectric lens was suggested as radiating elements. AVA has a broadband specification along with directive stable patterns at operational bandwidth. Combinational structure of substrate integrated waveguide topology by modified radiating element (AVAs) results to miniaturized size and acceptable radiation efficiency in whole of Ku‐Band. Presented array covers frequency range of 13–17.5 GHz (30%) with average gain of 14.2 dBi. The proposed beam‐steering antenna with compact size and good performance is capable to cover an angle range from −39 to 38° in whole operation frequency. This structure with unique configuration and specification can be a good candidate for beam‐forming application for wireless devices.